Parental views on state cannabis laws and marijuana use for their medically vulnerable children. (1st June 2019) - Wisk, Lauren E.; Levy, Sharon; Weitzman, Elissa R.
Highlights: Parents varied in the accuracy of their knowledge of state cannabis laws. Most parents believe marijuana use is risky for their medically vulnerable child. Yet 30% would approve of marijuana use if prescribed as medicine. Legal recreational use was associated with reduced parental agreement with medical benefits of marijuana. Abstract: Background: Given a rapidly changing policy landscape, we sought to characterize the effects of state marijuana laws on parents' views of marijuana use by their teenage children. Methods: Data are from 595 respondents to a nationally administered, web-based survey of parents of adolescents (ages 13–18 years) with any of three chronic conditions (type 1 diabetes, rheumatic disease, attention-deficit/hyperactivity disorder). Multivariate ordinal logistic regression was used to model the effects of parents' reports of state cannabis laws on their views toward marijuana use by their child. Results: While 89.9% said any marijuana use was risky for their child, 27.9% would approve of its use if prescribed as medicine. Parents reporting marijuana decriminalization (11.1%) were more amenable to teenage use, less concerned about how marijuana might impact their child's condition, more accepting of the safety of marijuana as medicine, and approved its use with a prescription. Parents reporting legal medical (35.6%) or recreational (5.7%) use were more likely to report that their child has tried or used marijuana regularly. Parents reporting legal recreational use were less likely to agree that marijuana has medical benefits for their child. Conclusions: Among parents of medically vulnerable children, perceiving state marijuana policies as more permissive is strongly associated with lower perceived riskiness of marijuana use for their children. State marijuana policies are changing with implications for how parents of medically vulnerable youth view and potentially govern marijuana use by their medically vulnerable children.